Theoretical Exploring Selective-Binding Mechanisms of JAK3 by 3D-QSAR, Molecular Dynamics Simulation and Free Energy Calculation - Zhu, Jingyu; Yu, Qianqian; Cai, Yanfei; Chen, Yun; Liu, Hui; Liang, Wenqing; Jin, Jian (Frontiers in Molecular Biosciences, 2020)
Janus kinase 3 (JAK3) plays a critical role in JAK/STAT signaling pathway and has become an attractive selective target for the treatment of immune-mediated disorders. Therefore, great efforts have been made on the development of JAK3 inhibitors, but it is still a great challenge to develop selective JAK3 inhibitors because of the high sequence homology with other kinases. In order to reveal the selective-binding mechanisms of JAK3 and find out the key structural features refer to specific JAK3 inhibition, a systematic computational method, including 3D-QSAR, molecular dynamics simulation and free energy calculations, was carried out on a series of JAK3 isoform-selective inhibitors. Then, necessary pharmacodynamic structures and key residues involved in efficient JAK3-inhibition were highlighted. Finally, ten novel JAK3 inhibitors were designed, the satisfactory predicted binding affinity to JAK3 of these analogous demonstrated that this study may facilitate the rational design of novel and selective JAK3 inhibitors.